1994
DOI: 10.2307/4088821
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolite Levels Predict Individual Body-Mass Changes in a Small Long-Distance Migrant, the Garden Warbler

Abstract: ABstRacr.-Change in body mass is an important measurement in many studies addressing changes in energy stores or condition. Usually, change in body mass is measured in birds caught twice, but this has a number of drawbacks (e.g. low number of retraps, retraps not representative of all first captures, adverse effects of first capture on body-mass development). Therefore, we investigated whether plasma metabolites correlate with body-mass change, and which metabolites could be used to predict body-mass change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 33 publications
8
141
1
1
Order By: Relevance
“…Numerous studies in captive passerines have shown that plasma metabolite concentrations reflect the physiological state of a bird in relation to fattening or fasting (DeGraw et al, 1979;Jenni-Eiermann and Jenni, 1994;Totzke and Bairlein, 1998). Jenni-Eiermann et al (2002b) showed that certain plasma metabolites (triglyceride and β-OH-butyrate) reflect seasonally changing metabolic processes among different life cycle stages (molt, migration, oversumering) in captive red knot (with birds on a similar diet to our high-fat diet).…”
Section: Plasma Metabolite Concentrations and Physiological Statementioning
confidence: 90%
See 1 more Smart Citation
“…Numerous studies in captive passerines have shown that plasma metabolite concentrations reflect the physiological state of a bird in relation to fattening or fasting (DeGraw et al, 1979;Jenni-Eiermann and Jenni, 1994;Totzke and Bairlein, 1998). Jenni-Eiermann et al (2002b) showed that certain plasma metabolites (triglyceride and β-OH-butyrate) reflect seasonally changing metabolic processes among different life cycle stages (molt, migration, oversumering) in captive red knot (with birds on a similar diet to our high-fat diet).…”
Section: Plasma Metabolite Concentrations and Physiological Statementioning
confidence: 90%
“…feeding vs fasting; Jenni-Eiermann and Jenni, 1994;Williams et al, 1999;Jenni and Schwilch, 2001), patterns of fuel utilization (Gannes, 2001;Jenni-Eiermann et al, 2002a) and inter-population or inter-site variation in fattening rates (Schaub and Jenni, 2001;Guglielmo et al, 2002). Direct validation of the use of plasma metabolite profiles to predict mass change in free-living birds will require independent assessment of fattening rates, which is difficult because of the problems associated with multiple recaptures of individuals, as outlined above (but see Guglielmo et al, 2005).…”
mentioning
confidence: 99%
“…Jenni-Eiermann and Jenni 1994). Although glucose plasma concentrations are often kept within a narrow range, low concentrations of glucose are usually recorded during fasting periods (Jenni-Eiermann and Jenni 1994;Alonso-Alvarez and Ferrer 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The higher values found in Northern shoveler (144.6 mg/dl) and European teal (126 mg/dl) compared to non-migratory birds, e.g. Black-necked swan (Cygnus melanocoryphus), 90 mg/dl (Artacho et al, 2007), may be due to elevation of triglyceride levels in migratory birds since they constitute the important source of energy mobilized from the fat deposits in order to permit them to migrate (Jenni-Eiermann et al, 2002;Jenni-Eiermann & Jenni, 1994).…”
Section: Plasma Biochemical Analysismentioning
confidence: 99%